ANALISIS PENGARUH KUALITAS AUDIT DAN PROFITABILITAS TERHADAP OPINI GOING CONCERN (Studi Empiris Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia saat pandemi COVID-19 tahun 2020-2021) - Daffa Dzulfikar Fauzy; Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2022)
This study aims to analyze the effect of audit quality and profitability on the acceptance of going concern opinions. The independent variables used in this study are audit quality and profitability, while the dependent variable used is going concern audit opinion.The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2020-2021. Purposive sampling method was used as a sampling method by using certain criteria with a total sample of 268 samples. Logistic regression analysis was used to test the hypothesis.The finding of this study showed that the audit quality had no significant effect on going concern audit opinions. Meanwhile, profitability has a significant negative effect on going concern audit opinions.